2011
DOI: 10.1039/c1ce05275f
|View full text |Cite
|
Sign up to set email alerts
|

Gradual spin crossover behaviour in a linear trinuclear FeII complex

Abstract: The synthesis, structures and magnetic properties of a new trinuclear spin crossover complex, [Fe II 3 (npt) 6 (EtOH) 4 (H 2 O) 2 ](ptol) 6 $4EtOH (1), and of its Co II (2 and 3) and Ni II (4) analogues, are reported here. The complexes were synthesized by reacting a 1,2,4-triazole-based ligand, 4-(4 0 -nitrophenyl)-1,2,4-triazole (npt), with the p-tolylsulfonate (ptol) metal salts in methanol or ethanol. Structural analyses revealed that all complexes are iomorphous and consist of a linear trinuclear core whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…The overall gradual SCO behavior of this material suggests weak cooperativity between molecules in the lattice. While structural analysis revealed a dense network of intramolecular interactions, the molecular species are well separated due to the bulky aromatic substituents on the furtrz ligands and the presence of many aromatic anions, meaning the communication between SCO units would be weak [16]. Furthermore, the relatively low spin transition temperature of this material is consistent with other polymeric species which contain bulky aromatic 1,2,4-triazole ligands, thought to contribute a lower overall ligand field strength [16,21].…”
Section: Synthesis Of Furanylidene-4h-124-triazol-4-amine (Furtrz)supporting
confidence: 58%
See 1 more Smart Citation
“…The overall gradual SCO behavior of this material suggests weak cooperativity between molecules in the lattice. While structural analysis revealed a dense network of intramolecular interactions, the molecular species are well separated due to the bulky aromatic substituents on the furtrz ligands and the presence of many aromatic anions, meaning the communication between SCO units would be weak [16]. Furthermore, the relatively low spin transition temperature of this material is consistent with other polymeric species which contain bulky aromatic 1,2,4-triazole ligands, thought to contribute a lower overall ligand field strength [16,21].…”
Section: Synthesis Of Furanylidene-4h-124-triazol-4-amine (Furtrz)supporting
confidence: 58%
“…Several trinuclear SCO materials have been reported, composed of the linear arrangement of iron(II) sites bridged by 1,2,4-triazole-type ligands of various 4-functionalisation [15][16][17][18]. These materials are particularly useful as a tool for modelling the SCO behavior of one-dimensional 1,2,4-triazole ligand chain materials as the central iron(II) sites are of the same [FeN 6 ] coordination environment [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A further study can be followed by synthesis of similar compounds with different degree of aromatic substitutions, either from the triazole ligands or from the counter anions. Furthermore, the relatively low transition temperature (120 K) for this compound is consistent with other similar discrete molecular species containing bulky aromatic 1,2,4-triazole ligands [19,[24][25][26].…”
Section: Magnetic Susceptibility and Mössbauer Spectroscopysupporting
confidence: 56%
“…The multiple intra-and inter-molecular H-bonding interactions found in the crystal lattice explain the strong cooperativity between the active Fe(II) centers. Interestingly, even though studies have shown that ligands with bulky aromatic substituents and aromatic anions might have a "dilute or separation effect" on the overall cooperativity of the SCO compounds [19,26]. The abrupt transition observed here stands for an example with the supramolecular interactions overcome the "aromatic dilute effect".…”
Section: Magnetic Susceptibility and Mössbauer Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation